2018
DOI: 10.1016/j.combustflame.2017.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and kinetics for the reaction of fulminic acid, HCNO, with an amino radical, NH2

Abstract: The reaction of fulminic acid, HCNO, with NH 2 radicals was studied using quantum chemical and theoretical kinetic methodologies. B3LYP/6-311++G(3df,2p) calculations combined with CCSD(T) energy calculations at the basis set limit reveal a complex potential energy surface, where only two entrance channels contribute significantly to the product formation. Transition state theory and RRKM master equation calculations find a rate coefficient ranging from 7.2  10-12 cm 3 molecule-1 s-1 at room temperature, to > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(57 reference statements)
1
1
0
Order By: Relevance
“…In 1986, Cummins et al confirmed its presence in Sgr B2 but this time at the millimeter spectrum bands. Nummelin et al et al, in 1998 and2000, further refined the detection of NH 2 CN in Sgr B2, specifying the emitting regions inside the molecular cloud (M for "Middle" and N for "North"), which was confirmed in 2014 by Belloche et al. In 2003, the presence of NH 2 CN in the central area of the Orion molecular complex (Orion KL) was reported by White et al, expanding the known presence of this molecule in our galaxy.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…In 1986, Cummins et al confirmed its presence in Sgr B2 but this time at the millimeter spectrum bands. Nummelin et al et al, in 1998 and2000, further refined the detection of NH 2 CN in Sgr B2, specifying the emitting regions inside the molecular cloud (M for "Middle" and N for "North"), which was confirmed in 2014 by Belloche et al. In 2003, the presence of NH 2 CN in the central area of the Orion molecular complex (Orion KL) was reported by White et al, expanding the known presence of this molecule in our galaxy.…”
Section: Introductionsupporting
confidence: 77%
“…However, the only way to form this product is through preceding protonation, which is not a robustly useful result. Fulminic acid and the amino radical reaction (•NH 2 + HCNO → NH 2 CN + •OH) were analyzed by Nguyen, Nguyen, & Vereecken (2018) for a temperature range of 700 to 2000 K at 1 atm. This reaction under the produced temperature and pressure (P&T) profiles is normally applicable in combustion studies.…”
Section: Known Reaction Mechanismsmentioning
confidence: 99%